Outcomes in the Year After First‐Ever Ischemic Stroke in a Bi‐Ethnic Population. Issue 2 (17th October 2022) - Lisabeth, Lynda D.; Brown, Devin L.; Dong, Liming; Zahuranec, Darin B.; Kwicklis, Madeline; Shi, Xu; Case, Erin; Smith, Melinda A.; Campbell, Morgan; Carrera, Joseph F.; Morgenstern, Lewis B.
Abstract : Objective: To investigate stroke outcomes at 3, 6, and 12 months post‐stroke overall and by ethnicity in a population‐based, longitudinal study. Methods: First‐ever ischemic strokes (2014–2019, n = 1, 332) among Mexican American persons (n = 807) and non‐Hispanic white persons (n = 525) were identified from the Brain Attack Surveillance in Corpus Christi Project. Data were collected from patient or proxy interviews (baseline, 3, 6, and 12 months post‐stroke) and medical records, including functional (activities of daily living/instrumental activities of daily living score), neurological (National Institutes of Health Stroke Scale), cognitive (Modified Mini‐Mental State Examination), and quality of life (QOL) outcomes (12‐domain Stroke‐specific Quality of Life scale). Outcome trajectories were analyzed using multivariable adjusted linear models, with generalized estimating equations to account for within‐subject correlations; interactions between ethnicity and time were included to investigate ethnic differences in outcomes. Results: The median age was 67 years (interquartile range 58, 78), 48.5% were women, and 60.6% were Mexican American persons. For all outcomes, significant improvement was seen between 3 and 6 months ( p  < 0.05 for all), with stability between 6 and 12 months. Mexican American persons had significantly worse outcomes compared with non‐Hispanic white persons at all time points (3, 6, and 12 months), with the exception of the National Institutes of Health Stroke Scale, which did not differ by ethnicity at 6 and 12 months, and the average change in outcomes did not vary significantly by ethnicity. Interpretation: Outcomes were at their worst at 3 months post‐stroke, and ethnic disparities were already present, suggesting the need for early assessment and strategies to improve outcomes and possibly reduce disparities. ANN NEUROL 2023;93:348–356